"Audyt miejski" jako narzędzie pomiaru jakości życia w miastach europejskich - Kusterka, Marta (Urban audit as a tool for assessing the quality of life in european cities, 2008)
Urban audit is a response to growing demand for an assessment of the quality of life in European cities. It provides reliable and comparative information, based on variables and indicators, on selected urban areas in Europe, mostly in the member states of the European Union. The comparison of cities by regional, national and European agencies as well as among the cities themselves, according to their position in Europe and certain development in different areas for example economic activity, employment, public transport, as well as disparities within them, is very useful, if not crucial, for policy measures. The paper presents urban audit as a useful and required tool for decision-making at European, national, regional and local level. The evolution, goals and structure of urban audit are presented in this study. Selected variables and indicators are also included.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 22, s. 135-142